CLEAN AND RESILIENT LONG-TERM RENEWABLE ENERGY STRATEGIES TO POWER INDONESIA’S NEW CAPITAL CITY: Capacity Expansion Modeling of Kalimantan Island - Ardin, Fadolly; Solihati, Keisha Dinya; Herawati, Augustin Rina; Turbiningsih, Oktaviani (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
In response to solve the crucial urban problems and severe environmental threats, the government of Indonesia announced plans to relocate the country’s government capital city from Jakarta (Java island) to the Penajam Paser, East Kalimantan (Borneo island) starting from 2024. Moreover, decision-makers are exploring long-term pathways to power the new Capital City (Nusantara) and broader Kalimantan Island to support clean energy transition commitment objectives. This study will analyze the potential energy transition pathways with a planning horizon to 2040 for expanding power generation capacity across Kalimantan and Nusantara to support this relocation. It aims to investigate the achievable renewable energy penetration levels in the generation mix and pathways to reach zero emissions for the capital city energy system. This study utilizes data-driven decision-making by computationally modeling the existing Kalimantan power system using the Engage™ open-access energy system planning tool. It explores future capacity expansion options by optimizing generation capacity, transmission investments, and integrating energy storage systems. The results are presented by discussing implications for energy sector planning and long-term energy scenarios for Nusantara and the island of Borneo. The results indicate that achieving a 100% renewable energy share in Borneo’s energy mix is possible by 2040, with 94.2% of electricity supplied from large hydro reservoirs. However, the lowest Levelized Cost of Electricity (LCOE) is not achieved under the 100% renewable energy scenario but rather under the 75% renewable energy share scenario, as the cost of some renewable options may exceed the cost of the cheapest fossil fuel power generation. The 100% renewable energy scenario in 2040 could increase the LCOE by 41% compared to the Business-as-Usual (BAU) scenario and it would require the highest investment costs. Moreover, the heavy reliance on large hydro reservoirs in the future energy systems of Nusantara and Borneo Island could lead to challenges related to land acquisition, social conflicts, and environmental degradation. This study also explores opportunities for clean energy development and investment in the new capital city plan, including potential infrastructure to support the energy transition, such as renewable energy sources, smart grids, and large-scale energy storage systems.